0011 Simulation On The Move. High-fidelity Transfer Training In A Moving Ambulance Is Used To Improve Non-technical Skills In A Multidisciplinary Team In An Isolated And Potentially Hostile Environment. (1st November 2014) - Norman, Aidan; Chadwick, Sean; Thomas, Jeremy
Abstract : Aims and specific learning outcomes for the works: To understand the improvement in multidisciplinary teamworking, technical and non-technical skills using mobile scenarios. To understand the logistics, pitfalls and safety aspects of mobile scenarios. To appreciate the multidisciplinary aspects of organising a mobile transfer course. Background/rationale: The need for inter-hospital transfer is increasing. 1 The transfer process is complex and often time-critical with a small team being formed in an isolated, mobile unit which must work together competently and professionally to ensure their own and patient safety. Roles and responsibilities during the transfer involve multiple technical and non-technical skills. This has been recognised by national bodies for some time. 2 Trainee anaesthetists are required to attend a transfer medicine course. 3 Lectures and static simulation are common and useful. However, advancing technology has enabled us to provide realistic transfer practice and critical incident management complementing the static and didactic part of the course. This gives the multidisciplinary team a greater appreciation of the nature of their tasks and each team member's role in the transfer. The decision-making process of return to base, staying put to manage an incident or proceeding to specialist centre for definitive treatment can be powerfully demonstrated. The importance of planning the transfer to prevent incidents has been enlightening to some candidates. This is reinforced by filming the process and debriefing after the scenario and confirmed through course feedback. Our transfer course has been regarded as useful and enjoyable. Developing the course requires the organisers to liaise with external services and improves their own understanding of the multidisciplinary nature of the transfer and their working environment. References: Dickinson P, Eynon CA. Improving the timeliness of time-critical transfers: removing "referral and acceptance" from the transfer pathway. Journal of The Intensive Care Society 2014; 15 (2): 104–108 AAGBI Guideline on Interhospital Transfer.www.aagbi.org/sites/default/files/interhospital09.pdf . Accessed 14th May 2014 Royal College of Anaesthetists. Anaesthesia Training Programme 2012. http://www.rcoa.ac.uk/system/files/TRG-CU-TRGProg2010_0.pdf . Accessed 14th May 2014